CarboScen: a tool to estimate carbon implications of land-usescenarios - Larjavaara, M.; Kanninen, M.; Alam, S.A.; Mäkinen, A.; Poeplau, C. (Wiley, 2017)
Land use directly impacts ecosystem carbon and indirectly influences atmospheric carbon. Computing ecosystem carbon for an area experiencing changes in land use is not trivial, as carbon densities change slowly after land‐use changes. We developed a tool, CarboScen, to estimate ecosystem carbon in landscapes. It is a simple tool typically used with an annual time step, and is based on carbon pools and densities. It assumes that carbon density asymptotically approaches a value, which is set for the land‐use type in question. We recommend CarboScen for landscapes with spatially relatively homogenous soils and climate, multiple land uses, and changes between these leading to slow changes in carbon densities because either soil organic carbon is included in the analysis or afforestation occurs. Thanks to its simplicity, it is particularly suitable for participatory planning, rapid assessment of REDD+ project potential, and educational use.